Does controlling for epicurean eating or the tendency to supersize food portions change the relationship between mindful eating and grazing? - Michail Mantzios; Katherine McAtamney; Harvey Regan; Karolina Kokocinska; Sophia Kauser; Eliza Kalika; Misba Hussain; Rebecca Keyte; Jeffrey Wood; Deborah Wallis; Helen Egan (Heliyon, 2024)
The study examines the potential for Epicurean eating to offer fresh perspectives on the predictive value of mindful eating. This research seeks to ascertain whether accounting for Epicurean eating (or its antithesis, supersizing), could influence the previously identified negative relationship between mindful eating and grazing habits. In a cross-sectional study, 419 participants completed questionnaires on epicurean eating, grazing, and mindful eating. The findings suggested mindful eating and epicurean eating were significantly associated with grazing, with both variables accounting for a significant amount of variance in grazing. Further analysis of the mindful eating subscales showed that eating without distraction, eating with awareness, and hunger and satiety cues accounted for this association with grazing when epicurean eating was included. Finally, whilst eating without distraction, eating with awareness, and hunger and satiety cues were associated with grazing, preference for supersizing did not account for a significant amount of variance in the relationship with grazing. The complex interplay between grazing and mindful eating becomes more apparent when considering the influence of epicurean eating. Exploring cross-cultural factors through additional research could provide valuable insights into the dynamics of epicurean eating and grazing. Simultaneously, incorporating alternative mindful eating scales may yield a more nuanced interpretation of mindful eating. Collectively, these avenues of inquiry warrant further investigation. Limitations and future directions are discussed.